2015
DOI: 10.1021/acs.jmedchem.5b00289
|View full text |Cite
|
Sign up to set email alerts
|

N-Benzoyl-1,5-benzothiazepine and Its S-Oxide as Vasopressin Receptor Ligands: Insight into the Active Stereochemistry around the Seven-Membered Ring

Abstract: The stereochemistry of N-benzoyl-1,5-benzothiazepine and its S-oxide derivatives as vasopressin receptor ligands was examined in detail by freezing the conformation with a methyl group at the C6 or C9 of 1,5-benzothiazepine. It was revealed that the active forms recognized by the receptors are (cis,aS) for 1,5-benzothiazepine (5-7)-II and (cis,1S,aS) (syn) for its S-oxide (8-10)-II. The C9-methyl derivative of 1,5-benzothiazepine S-oxide (10-II) was designed and synthesized, achieving the putative active syn-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Many of the vaptan class of drugs contain a preserved structure, i.e., a benzo-fused seven-membered-ring nitrogen heterocycle (e.g., 1-benzazepine, 1,4-benzodiazepine) linked through N-1 to a substituted benzoyl group. In our previous papers, new VP receptor ligands with 1,5-benzodiazepine ( 1 ) and 1,5-benzothiazepine nuclei ( 2 , 3 ) (Figure ) were described to reveal the importance of the stereochemistry around the seven-membered ring for exerting their biological activity. In particular, the axial chirality (a S /a R ) based on the Ar–N­(CO) (sp 2 –sp 2 ) axis was clarified to be crucial by freezing the conformation in molecules with an ortho substituent (e.g., R = CH 3 , Cl); the (a S ) form was the eutomer (active enantiomer).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the vaptan class of drugs contain a preserved structure, i.e., a benzo-fused seven-membered-ring nitrogen heterocycle (e.g., 1-benzazepine, 1,4-benzodiazepine) linked through N-1 to a substituted benzoyl group. In our previous papers, new VP receptor ligands with 1,5-benzodiazepine ( 1 ) and 1,5-benzothiazepine nuclei ( 2 , 3 ) (Figure ) were described to reveal the importance of the stereochemistry around the seven-membered ring for exerting their biological activity. In particular, the axial chirality (a S /a R ) based on the Ar–N­(CO) (sp 2 –sp 2 ) axis was clarified to be crucial by freezing the conformation in molecules with an ortho substituent (e.g., R = CH 3 , Cl); the (a S ) form was the eutomer (active enantiomer).…”
Section: Introductionmentioning
confidence: 99%
“…The racemates (R & S) were then separated by chiral HPLC and their absolute configuration was assigned by performing X-ray analysis. [50] S C H E M E 1 Synthesis of Inspired from the literature reports and medicinal importance of S-oxide derivatives of different drugs, Makino and co-workers unfolded an efficient synthetic protocol for the synthesis of S-oxide-1,5-benzothiazepines from various substituted 1,5-benzothaizepines (72) by employing modified Unge's catalytic system. The reaction conditions were optimized for the catalyst, ratio of ligand and catalyst and amount of water in the solvent and it was concluded that Ti(O-i Pr) 4 (0.1 eqiv) as a chiral catalyst, (R,R)-diethyl tartrate (0.5 equiv), using Ti(O-i Pr) 4 to (R,R)-diethyl tartrate in the ratio of 1:1, i Pr 2 NEt (1.3 equiv) as a base, 80% cumene hydroperoxide (1.3 equiv) in toluene at 0 C were the best-suited conditions to afford the final compounds (74) in high yield along with high ee that is, 95% and 99%, respectively (Scheme 16, entry 2) .…”
Section: Enantioselective Synthesis Of 15-benzothiazepinesmentioning
confidence: 99%
“…In our previous papers, , atropisomerism in N -benzoyl-1,5-benzodiazepines ( 1 , X = NCH 3 ) and N -benzoyl-1,5-benzothiazepines ( 2 , X = S; 3 , X = S*=O) as VP receptor ligands was described (Figure ), in which the E / Z -amide rotamers around the N−C­(=O) bond and (a S )/(a R )-axial isomers based on the Ar−N­(CO) (sp 2 –sp 2 ) axis were considered (Figure ). In general, however, for the E / Z -amide isomers, compounds 1 – 3 all exist predominantly in the E -form, and the Z -isomer was negligible in the 1 H NMR spectrum .…”
Section: Introductionmentioning
confidence: 97%
“…Those studies led to the finding of the importance of axial chirality in exerting the biological activity of the vaptan class of VP receptor ligands, exhibiting the active structure (eutomer) with the ( E ,a S )-form of the types 1 and 2 (Figure ). , …”
Section: Introductionmentioning
confidence: 99%